Background seismicity rate at subduction zones linked to slab‐bending‐related hydration. Issue 17 (12th September 2015) - Nishikawa, Tomoaki; Ide, Satoshi
Abstract Tectonic properties strongly control variations in seismicity among subduction zones. In particular, fluid distribution in subduction zones influences earthquake occurrence, and it varies among subduction zones due to variations in fluid sources such as hydrated oceanic plates. However, the relationship between variations in fluid distribution and variations in seismicity among subduction zones is unclear. Here we divide Earth's subduction zones into 111 regions and estimate background seismicity rates using the epidemic type aftershock sequence model. We demonstrate that background seismicity rate correlates to the amount of bending of the incoming oceanic plate, which in turn is related to the hydration of oceanic plates via slab‐bending‐related faults. Regions with large bending may have high‐seismicity rates because a strongly hydrated oceanic plate causes high pore fluid pressure and reduces the strength of the plate interface. We suggest that variations in fluid distribution can also cause variations in seismicity in subduction zones.